Comparable analysis of an investigation of biomass energetic properties - Tychanicz, Maria; Wilk, Joanna; Grosicki, Sebastian (Advances in Mechanical and Materials Engineering)
his paper presents the comparable analysis of the investigation of energetic properties of two types of biomass. The research was made on the manual and semi-automatic oxygen-bomb calorimeter KL-12Mn. The basic energetic properties include calorific value and heating value. Calculations were made according to the PN-ISO 1928 standard. The research was made for basket willow and paulownia tomentosa samples. To determine the average value of each parameter samples of each kind of biomass were researched three times on both devices, which increased the accuracy of methods. The paper also includes the uncertainty analysis.